2014
DOI: 10.1122/1.4826939
|View full text |Cite
|
Sign up to set email alerts
|

Large amplitude oscillatory microrheology

Abstract: SynopsisWe study the motion of a colloidal particle as it is driven by an oscillating external force of arbitrary amplitude and frequency through a colloidal dispersion. Large amplitude oscillatory flows (LAOFs) are examined predominantly from a phenomenological perspective in which experimental measurements inform constitutive models. Here, we investigate a LAOF from a microstructural perspective by connecting motion of the probe particle to the material response while making no assumptions a priori about how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…However, the additional attraction provided by the DNA hybridization leads to a slightly narrower S(q) at higher volume fractions for the DNA-NPs. This is in agreement with the findings that strongly attracting colloids simply show more rapid kinetic arrest when quenched into the spinodal decomposition region 3, 14 than weaker short-ranged attractive interactions of less than a few k B T. 47 It is also interesting to note that the cord analysis data (Table 1) suggest that the PEG-NP gels are more compact than the DNA-NP gels. In all three volume-fractions studied the average pore sizes are systematically larger and the gel arms smaller in the PEG-NP gels.…”
supporting
confidence: 88%
“…However, the additional attraction provided by the DNA hybridization leads to a slightly narrower S(q) at higher volume fractions for the DNA-NPs. This is in agreement with the findings that strongly attracting colloids simply show more rapid kinetic arrest when quenched into the spinodal decomposition region 3, 14 than weaker short-ranged attractive interactions of less than a few k B T. 47 It is also interesting to note that the cord analysis data (Table 1) suggest that the PEG-NP gels are more compact than the DNA-NP gels. In all three volume-fractions studied the average pore sizes are systematically larger and the gel arms smaller in the PEG-NP gels.…”
supporting
confidence: 88%
“…They observed that as the external force increases the distribution of colloidal particles around the probe becomes more anisotropic, with large accumulation of particles in front and a depleted zone or wake behind the probe. This work was extended to consider the effect of pair hydrodynamic interactions in dilute suspension [Khair & Brady, 2006], the role of probe particle's shape [Khair & Brady, 2008], relation between stress and force-induced diffusivity of the probe [Zia & Brady, 2012], and the case of having an oscillating external force/velocity [Swan et al, 2014]. The predictions of the dilute theories are in qualitative agreement with available experimental work [Sriram et al, 2010] and Brownian Dynamics simulations [Carpen & Brady, 2005].…”
Section: Introductionsupporting
confidence: 52%
“…We show that the source of the dispersion in CF is the hydrodynamic interactions of the probe with its neighboring bath particles. This is the first study that takes into account the effect of hydrodynamic dispersion on the structure and viscosity of colloidal suspensions in active microrheology; the previous theories ignore this effect by either assuming the suspension is dilute and the interactions are limited to pair particles [Squires & Brady, 2005;Khair & Brady, 2006;Swan & Zia, 2013;Swan et al, 2014], or the HI is entirely ignored [Gazuz et al, 2009;Voigtmann & Fuchs, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…More fundamentally, it provides a compelling connection between fluctuation and dissipation away from equilibrium, extending Einstein's equilibrium fluctuation‐dissipation theory of Brownian motion to strong departures from equilibrium (H. C. W. Chu and R. N. Zia, in preparation). Experimental studies, theoretical models, and dynamic simulations of active microrheology have recovered steady‐state non‐Newtonian behaviors measured via traditional shear rheology, including flow thinning and thickening, flow‐induced diffusion, normal stress differences, and linear viscoelasticity . Comparison between rheological measurements obtained via viscometric flows, for example, simple shear, and those obtained via microrheology, reveal many qualitative similarities as well as important differences.…”
Section: Introductionmentioning
confidence: 77%